DRIVERS FOR FOOD SECURITY AND SUSTAINABLE AGRICULTURE: AN OVERVIEW OF RECENT RESEARCH - G. Panaedova; S. Gorlov (Вестник Северо-Кавказского федерального университета, 2022)
In the context of global economic instability, the relevance ofproblems of ensuring food security and sustainable agricultural development at the international and national levels is becoming more relevant. Existing methods for assessing the state of food security and sustainable development have some peculiarities: first, they are often static, and secondly, they include a separate list of indicators that are difficult to interpret systematically when conducting an analysis. The methodological review of modern foreign research has shown that in assessing food security, sustainability should be considered as part of a long-term time measurement. From this perspective, the concept of sustainable nutrition can play a key role as a goal and way to maintain nutritional well-being and health while ensuring sustainable food security. Various aspects of food security and programs in modern policies may lead to increased food security in the future.